Livestock and food security in smallholder production systems in Africa: Beyond meat and milk - Lebbie, S.H.B. (South African Society of Animal Science, 1996)
Today, about 800 million people experience hunger and malnutrition. The major underlying factors include inadequate food supply due to inadequate production and distribution, and low incomes. animal agriculture is crucial to the enhancement of food security and sustainable agricultural Development in Africa and in the rest of the "developing" world. Livestock provide high quality food in the form of meat, milk and eggs. Above these, they contribute to food production through nutrient cycling and use of draught power for crop production; they provide opportunities for employment and earning cash income; they meet the socio-cultural needs of the people who keep them. The multiple functions of livestock have, however, not been fully recognised as a result of cultural prejudices and lack of understanding. These prejudices manifest themselves in the criticism against animal agriculture and the declining international support for animal agriculture in the developing world, especially in SSA. This situation needs to be reversed, and needs to be done quickly, because the livelihood of majority of resource poor people in the developing countries depends on sustainable animal agriculture.